2010
DOI: 10.1002/cssc.201000090
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Infrared Study of the Role of PEG in Stabilizing Silica‐Supported Amines for CO2 Capture

Abstract: The CO(2) capture capacity, adsorption mechanism, and degradation characteristics of two sorbents, silica-supported tetraethylenepentamine (TEPA/SiO(2)) and polyethylene-glycol-modified TEPA/SiO(2) (PEG/TEPA/SiO(2)), are studied by diffuse reflectance infrared Fourier transform spectroscopy and mass spectrometry. The CO(2) capture capacities of TEPA/SiO(2) and PEG/TEPA/SiO(2) are determined to be 2087 and 1110 micromol CO(2) g(-1) sorbent, respectively. Both sorbents adsorb CO(2) as hydrogen-bonding species, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 37 publications
7
119
1
2
Order By: Relevance
“…We found that adsorption half time, which is defined as the time required for the sorbents to reach half of their saturated adsorption capacities, can serve as a semiquantitative indicator of the overall adsorption and diffusion kinetics. 55,56 Analysis of the CO 2 profiles for amine sorbents in the literature 52,54,55,57 revealed that the sorbents' adsorption half times were within the range of those of our TEPA films, between 0.28 and 0.42 min. 52,54,55,57 Comparable adsorption half times for the sorbents and films suggests similar adsorption kinetics for immobilized and liquid amines, in spite of potential diffusion effects in the immobilized amine sorbent.…”
Section: ■ Introductionmentioning
confidence: 83%
“…We found that adsorption half time, which is defined as the time required for the sorbents to reach half of their saturated adsorption capacities, can serve as a semiquantitative indicator of the overall adsorption and diffusion kinetics. 55,56 Analysis of the CO 2 profiles for amine sorbents in the literature 52,54,55,57 revealed that the sorbents' adsorption half times were within the range of those of our TEPA films, between 0.28 and 0.42 min. 52,54,55,57 Comparable adsorption half times for the sorbents and films suggests similar adsorption kinetics for immobilized and liquid amines, in spite of potential diffusion effects in the immobilized amine sorbent.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Alongside amine leaching it is possible that the active sites are deactivating through the formation of carboxylate/carbamate/urea species. This effect was investigated by Tanthana et al [22] through an infra-red spectroscopy study. The rate of amine leaching was lower at lower loadings.…”
Section: Ranking Of Impregnated Materials As Candidates For Co 2 Adsomentioning
confidence: 96%
“…Besides, the addition of PEG also increased the fraction of weakly adsorbed CO 2 species (Zwitterion as shown in Eq. (1)), which was related to a hydrogen-bonding species (i.e., NH 2 -O) (Tanthana and Chuang, 2010). Plaza et al (2007Plaza et al ( , 2008) studied CO 2 capture using activated carbon and alumina impregnated with various types of amines including primary and secondary alkylamines such as DETA, pentaethylenehexamine (PEHA) and PEI, alkanolamines such as diisopropanolamine (DIPA), sterically hindered 2-amino-2-methyl-1,3-propanediol (AMPD), and triethanolamine (TEA).…”
Section: Fig 3 (Continued)mentioning
confidence: 99%